Psychological Reactance and Persuasive Health Communication: A Review of the Literature - Reynolds-Tylus, Tobias (Frontiers in Communication, 2019)
Psychological reactance theory is a commonly relied upon framework for understanding audience members’ resistance to persuasive health messages. This review article provides an overview of reactance research in the context of persuasive health communication. The article begins with an overview of psychological reactance theory. The major concepts of the theory are discussed, as well as recent developments by communication researchers in measuring reactance. Following this, contemporary reactance research in the context of persuasive health communication is summarized. An emphasis is placed on research examining message features associated with reactance, as well as the moderating role of trait reactance. The article concludes with a discussion of several promising directions for future research.